Peran Perempuan dan Era Baru di Nangroe Aceh Darussalam - Sri Lestari Wahyuningroem (Antropologi Indonesia, 2005)
In the midst of prolong conflict and the delay of reconciliation, Indonesian government provides a special autonomy to the Aceh people to implement Islamic laws (sharia') in the sociopolitical realms. Yet, for Aceh women the implementation of sharia' creates discriminative regulations such as enforcement to wear jilbab and curfew for them. Many recent political policies are totally disregarding Aceh women as part of the Aceh society. Various local regulations (qanun) that proposed by local government are not gender-sensitive and put forward violence in doing conflict resolution. Local autonomy brings the oppression of women's roles in the society. Historically, Aceh women have significant roles in shaping cultural identity of Aceh society. In the past, the interpretation of sharia' recognized and supported women's leadership in the society. Hence, a new approach to put back women's public roles in order to participate in reconciliation process of the Aceh society is needed. Key words: Aceh special autonomy; Islamic laws; women's role; gender inequality